Comparison of 2-D and 3-D full waveform inversion imaging using wide-angle seismic data from the Deep Galicia Margin. Issue 1 (11th May 2021) - Boddupalli, Bhargav; Minshull, Tim A; Morgan, Joanna; Bayrakci, Gaye; Klaeschen, Dirk
SUMMARY: Full waveform inversion (FWI) is a data-fitting technique capable of generating high-resolution velocity models with a resolution down to half the seismic wavelength. FWI is applied typically to densely sampled seismic data. In this study, we applied FWI to 3-D wide-angle seismic data acquired using sparsely spaced ocean bottom seismometers (OBSs) from the Deep Galicia Margin west of Iberia. Our data set samples the S-reflector, a low-angle detachment present in this area. Here we highlight differences between 2-D, 2.5-D and 3-D-FWI performances using a real sparsely spaced data set. We performed 3-D FWI in the time domain and compared the results with 2-D and 2.5-D FWI results from a profile through the 3-D model. When overlaid on multichannel seismic images, the 3-D FWI results constrain better the complex faulting within the pre- and syn-rift sediments and crystalline crust compared to the 2-D result. Furthermore, we estimate variable serpentinization of the upper mantle below the S-reflector along the profile using 3-D FWI, reaching a maximum of 45 per cent. Differences in the data residuals of the 2-D, 2.5-D and 3-D inversions suggest that 2-D inversion can be prone to overfitting when using a sparse data set. To validate our results, we performed tests to recover the anomalies introduced by the inversions in the final models using synthetic data sets. Based on our comparison of the velocity models, we conclude that the use of 3-D data can partially mitigate the problem of receiver sparsity in FWI.